Furanoids from the Gymnadenia conopsea (Orchidaceae) seed germination supporting fungus Ceratobasidium sp. (GS2) - Shi, Lixin; Han, Li; Zhao, Zeyu; Li, Qi; Wang, Yanduo; Ding, Gang; Xing, Xiaoke (Frontiers in Microbiology, 2022)
Five furanoids including a new analog (S)-1,4-di(furan-2-yl)-2-hydroxybutane-1,4-dione (1) together with four known ones, rhizosolaniol (2), 5-hydroxymethylfurfural (3), 2-furoic acid (4) and (2-furyl) oxoacetamide (5), were isolated from the fungal strain Ceratobasidium sp. (GS2) inducing seed germination of the endangered medicinal plant Gymnadenia conopsea of Orchidaceae. The structure of new furanoid 1 was determined mainly based on HR-ESI-MS and NMR spectral data. Modified Mosher’s reactions were used to establish the stereochemistry of the hydroxyl group in 1, which was not stable in Mosher’s reagents and transformed into four analogs 6-9. These degraded products (6-9) were elucidated based on UPLC-Q-TOF-MS/MS analysis, and compound 8 was further isolated from the degraded mixture and its structure was characterized through NMR experiments. Therefore, the absolute configuration of compound 1 was determined by electronic circular dichroism (ECD) combined with quantum-chemical calculations adopting time-dependent density functional theory (TDDFT). Compounds 1-5, and 8 showed weak antioxidant activities, and compounds 2-4 displayed phytotoxicity on punctured detached green foxtail leaves. In addition, compounds 3 and 4 strongly showed inhibition activities on the seed germination of G. conopsea. This was the first chemical investigation of the symbiotic fungus of G. conopsea.